Dry matter yield and tillering of brachiarias sown at depths intercropped with corn - Gazola, Rodolfo de Niro [UNESP]; Mello, Luiz Malcolm Mano de [UNESP]; Dinalli, Raíssa Pereira [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Celestrino, Thiago de Souza [UNESP]; Dupas, Elisângela [UNESP]; Garcia, Cássia Maria de Paula [UNESP] (Universidade Federal de Santa Maria, 2014)
Considering the growth of forage production in crop-livestock system and the possibility of sowing forages at different depths, it's still necessary more research to understand the development of the main forage plants. This study aimed to evaluate the tillering and dry matter yield of two brachiaria species under different depths of seed deposition intercropped with corn in integrated crop-livestock production in the Cerrado region. The experiment was conducted in no-tillage system in Selvíria - Mato Grosso do Sul State, in an Oxisol, clayey. The experimental design was randomized blocks in factorial scheme 2x3, with four replications. The treatments were two species of brachiaria (Brachiaria brizantha cv. 'Marandú' and Brachiaria ruziziensis), whose seeds were mixed with fertilizer from corn, and three different depths (8, 10 and 16cm) of fertilizer deposition. The deposition of brachiarias seeds to 16cm depth resulted in lower stand of tillers and dry matter yield. The tillering of forages was influenced by the phases of the corn cycle, with trend towards stabilization in closing between the lines of culture and taken up in the issuance of tillers at the end of the cycle

Considerando o crescimento da produção de forragem no sistema integração lavoura-pecuária e a possibilidade de consorciação de milho com forrageiras semeadas em diferentes profundidades, ainda são necessárias mais pesquisas para entender o desenvolvimento das principais forrageiras. Objetivou-se neste trabalho avaliar o perfilhamento e a produtividade de matéria seca de duas espécies de braquiárias submetidas a profundidades de deposição das sementes em consórcio com milho, em sistema de integração lavoura-pecuária, na região do Cerrado. O experimento foi conduzido em sistema plantio direto no município de Selvíria - MS, num LATOSSOLO VERMELHO Distroférrico, textura argilosa. O delineamento experimental foi o de blocos ao acaso, em esquema fatorial 2x3, com quatro repetições. Os tratamentos foram duas espécies de braquiárias (Brachiaria brizantha cv. 'Marandu' e Brachiaria ruziziensis), cujas sementes foram misturadas ao fertilizante do milho, e três profundidades (8, 10 e 16cm) de deposição do fertilizante + sementes. A deposição das sementes de braquiárias a 16cm de profundidade resultou em menor número de perfilhos e produtividade de matéria seca. O perfilhamento das forrageiras foi influenciado pelo ciclo do milho, com tendência de estabilização no fechamento das entre linhas da cultura e retomada na emissão de perfilhos no final do ciclo
Keywords: Brachiaria brizantha; Brachiaria ruziziensis; integração lavoura-pecuária; densidade populacional de perfilhos; Brachiaria brizantha; Brachiaria ruziziensis; crop-livestock integration; tiller population density